Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.52700/assap.v3i1.155
|View full text |Cite
|
Sign up to set email alerts
|

Revealed Comparative Advantage and Pakistan’s Global Leather Products Potential among Selected Leather Exporters: New Evidence from Kaplan-Meier Survival Function

Abstract: One Of the key objectives of this study is to examine Pakistan’s global leather and leather products competitiveness by utilizing Balassa revealed comparative advantage (BRCA) indices and revealed symmetric comparative advantage indices (RSCA) from 1996 to 2020. Pakistan’s agricultural sector is contributing 19.5% of GDP while, livestock is ranked as the second largest sector of the agriculture sector with a 50% share of value-added goods, and together 10.8% share in GDP. The abundance of raw materials and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…This result supports the fact that political instability is a harmful thing for GDP growth inPakistan even in case of whole world. This result is consistent with (Aisen & Veiga, 2013;Alesina, Özler, Roubini, & Swagel, 1996;Siddique, e Ali, Sajid, Khan, & Irshad, 2022).…”
Section: Unites Roots Testsupporting
confidence: 90%
“…This result supports the fact that political instability is a harmful thing for GDP growth inPakistan even in case of whole world. This result is consistent with (Aisen & Veiga, 2013;Alesina, Özler, Roubini, & Swagel, 1996;Siddique, e Ali, Sajid, Khan, & Irshad, 2022).…”
Section: Unites Roots Testsupporting
confidence: 90%
“…Available literature has demonstrated that lack of export competitiveness is also considered as one of the prominent reasons of Pakistan's stagnant exports (e.g. Siddique, et al 2022;Kausar, 2015;Paravisini, et al 2015;Amiti and Weinstein, 2011). Export competitiveness is measured in different ways such as export share in global trade and revealed comparative advantage which is provided by United Nations Conference on Trade and Development (UNCTAD) 1 has computed index to measure export competitiveness by product groups.…”
Section: Export Competitivenessmentioning
confidence: 99%
“…The leather industry is considered one of the key exporting industries in Pakistan second only to the textile sector. This sector contributes more than 20% to GDP and holds significant potential for attracting foreign exchange through improvements in quality and diversification of leather products [1]. Leather manufacturing is a substantial manufacturing process in the Pakistan, with 700 tanneries located in major three cities Sialkot, Karachi and Lahore [2].…”
Section: Introductionmentioning
confidence: 99%